Propuesta de un sistema de control interno basado en el modelo Coso I proceso de tesorería de una empresa productora de comidas rápidas en Palmira. (2022)
Organizations face challenges, making it necessary for them to have clear goals, in addition to efficiency in managing money; Therefore, a fast food company in the city of Palmira is chosen, which does not have an internal control system for the treasury area, leading to the proposal of an internal control system, through the COSO I model, serving of guidance in the development of its objectives and identifying the current situation, based on the most critical risks and points in which the company faces.